Blood lipids of the small octopus Octopus tehuelchus (Mollusca: Cephalopoda) at different stages of sexual maturation - Heras, Horacio (1989)
Fil: Heras, Horacio. Instituto de Investigaciones Bioquímicas de La Plata (INIBIOLP); UNLP